Trust in leadership and perceptions of justice in fostering employee commitment - González-Cánovas, Alejandro; Trillo, Alejandra; Bretones, Francisco D.; Fernández-Millán, Juan M. (Frontiers in Psychology, 2024)
In a period of uncertainty, trust in leadership and perceptions of fairness have emerged as pivotal factors for fostering employee identification and affective commitment. Drawing from authentic leadership theory, this leadership style is identified as a crucial antecedent of affective commitment, examining the mediating role of distributive justice and the moderating role of interactional justice. A quantitative approach was employed, utilizing data from 302 questionnaires completed by Spanish retail workers. For data analysis, SPSS v.25 was used to generate descriptive statistics, while partial least squares structural equation modeling was applied to test the proposed hypotheses. Our findings revealed that authentic leadership is positively associated with the development of affective commitment, with distributive justice acting as a mediating factor between the two. Furthermore, interactional justice negatively moderates the relationship between distributive justice and affective commitment. Contrary to initial expectations, the second moderation, between authentic leadership and affective commitment, was not found to be significant. The research concludes by discussing the practical implications of the results.